2019
DOI: 10.3389/fphys.2019.01028
|View full text |Cite
|
Sign up to set email alerts
|

Baveno Criteria Safely Identify Patients With Compensated Advanced Chronic Liver Disease Who Can Avoid Variceal Screening Endoscopy: A Diagnostic Test Accuracy Meta-Analysis

Abstract: Background: The Baveno VI Consensus Workshop defined criteria (liver stiffness measured by transient elastography <20 kPa and platelet count >150 × 10 9 cells/L) to identify those patients with compensated advanced chronic liver diseases (cACLD) who are unlikely to have varices needing treatment (VNTs) and can safely avoid variceal screening endoscopy. This meta-analysis aimed to quantify the safety and efficacy of these criteria in suspected cACLD with liver stiffness >10 kPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 48 publications
1
17
0
2
Order By: Relevance
“…Thereafter, some studies tried to optimize the thresholds to increase the number of EGDs that could be avoided. The Expanded Baveno VI criteria (PLT count >110 × 10 −9 /L and LSM < 25 kPa) seemed to spare more EGDs at a proportion of about 30.5%‐51.7% 8‐11 . The other two most widely validated criteria are “PLT > 125/LSM < 25” and ‘stepwise PLT‐MELD’ strategy (platelet >150 × 10 −9 /L or platelet ≤150 × 10 −9 /L but MELD = 6), showing 14%‐28% increase in the proportion of spared endoscopies compared to Baveno VI criteria 6,9 …”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, some studies tried to optimize the thresholds to increase the number of EGDs that could be avoided. The Expanded Baveno VI criteria (PLT count >110 × 10 −9 /L and LSM < 25 kPa) seemed to spare more EGDs at a proportion of about 30.5%‐51.7% 8‐11 . The other two most widely validated criteria are “PLT > 125/LSM < 25” and ‘stepwise PLT‐MELD’ strategy (platelet >150 × 10 −9 /L or platelet ≤150 × 10 −9 /L but MELD = 6), showing 14%‐28% increase in the proportion of spared endoscopies compared to Baveno VI criteria 6,9 …”
Section: Introductionmentioning
confidence: 99%
“…Another meta-analysis, including 13 studies and 4464 patients with cACLD, yielded similar results; the pooled rate of missing HRV was 0.3% and 32.8% of the gastroscopies could be avoided. The sensitivity, specificity, and area under the receiver operating curve of the Baveno VI criteria were 97%, 41%, and 96%, respectively [ 29 ]. These studies demonstrated that the Baveno VI criteria is a reliable method for stratifying the risk of EV and sparing gastroscopies in patients with cACLD or compensated cirrhosis.…”
Section: The Validation Of Baveno VI Criteriamentioning
confidence: 99%
“…The Baveno VI criteria spared 39% and 30% of gastroscopies in patients with PBC and PSC, respectively, without missing HRV [ 33 ]. In a recent meta-analysis involving patients with cACLD due to HCV, HBV infection, NAFLD, and alcohol liver disease, the Baveno VI criteria missed HRVs at a rate of 0.0%, 1.2%, 0.0%, and 0.0%, respectively [ 29 ]. In addition, gastroscopies were spared in 24.2%, 24.9%, 38.6%, and 27.0% of patients, respectively.…”
Section: The Validation Of Baveno VI Criteriamentioning
confidence: 99%
See 2 more Smart Citations